Dessecação pré colheita do feijão mouro e seus efeitos sobre a produtividade - Fank, Lucas Antonio Patricio (2023)
Beans (Phaseolus vulgaris L.) are a crop of extreme economic and social importance, as they are one of the staple foods of Brazilians, being one of the main sources of protein, especially for low-income families. Brazil stands out among the largest producers, without significant export volumes, as domestic consumption of the product is almost total, but it is a market that can develop. Due to the great demand and cultivation of beans, desiccation management is used to standardize and anticipate the harvest. An important factor to be observed when making a decision is the degree of physiological maturity, so that quality and productivity are not compromised. The experiment was carried out in the municipality of Dois Vizinhos, at the Federal Technological University of Paraná, located in the Southwest of Paraná, in the 23/23 harvest. The aim of the work was to evaluate the desiccation of beans during preharvest, evaluating its effects on different degrees of maturation of the phenological stage. The experimental design was carried out in randomized blocks, with five treatments, four of which were desiccated on different days of plant development, and a control without desiccation. The data obtained amounts to a difference of 14 bags between the best and worst results.